Becoming Your Own Therapist: Expanded edition including Make Your Mind an Ocean/ (Acc: D 499) - Thubten Yeshe, 1935-1984.; Thubten Yeshe, 1935-1984.; Ribush, Nicholas (Boston : Lama Yeshe Wisdom Archive, 2010)
"In 1975, Lama Yeshe embarked on his most extensive world tour ever. During this time he delivered many public lectures to audiences of people who were largely unacquainted with Buddhism and hearing a Tibetan lama for the first time. Thus the teachings in this book are an excellent introduction to Tibetan Buddhism and the Buddha's teachings in general"--Provided by publisher.
Keywords: Buddhism; Buddhism